Association of longitudinal trends in thyroid function with incident carotid atherosclerosis in middle-aged and older euthyroid subjects: the Tianjin Chronic Low-Grade Systemic Inflammation and Health (TCLSIH) cohort study. (23rd January 2022) - Gu, Yeqing; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Zhang, Shunming; Wang, Yawen; Zhang, Tingjing; Wang, Xuena; Sun, Shaomei; Wang, Xing; Jia, Qiyu; et al.
Abstract: Background: Previous studies have posited that an association exists between thyroid function and the heart and vasculature. It remains unclear, however, whether longitudinal trends in thyroid function contribute to the development of atherosclerosis. We conducted a cohort study to examine the association of longitudinal trends in thyroid function with incident carotid atherosclerosis (CA) in middle-aged and older euthyroid subjects. Methods: This cohort study's participants were recruited from the Tianjin Chronic Low-grade Systemic Inflammation and Health Cohort Study in Tianjin, China. Free triiodothyronine (FT3), thyroxine (FT4) and thyroid-stimulating hormone (TSH) were measured using chemiluminescence immunoassay. CA was assessed using carotid ultrasonography. Thyroid function and ultrasonography were assessed yearly during follow-up. Multivariable Cox proportional hazards regression models were used to assess the association between thyroid function and incident CA. Results: A total of 3, 181 participants were enrolled in the cohort study. Within 7, 762 person-years of follow-up, 944 participants developed CA, the incidence rate of CA was 122 per 1, 000 person-years. The fully adjusted hazards ratios (95% confidence interval) of CA for per 1-unit increase in changes of FT3, FT4 and TSH were 1.34(1.22–1.47), 1.22(1.19–1.26) and 0.92 (0.77–1.09) ( P < 0.0001, <0.0001 and = 0.32, respectively), respectively. Similar significant associations between mean levels of FT3 and FT4 and incident CA were observed. However, baseline thyroid function was not associated with incident CA. Conclusions: These findings suggest that higher mean levels and higher values of changes in thyroid hormones were associated with a higher risk of incident CA in middle-aged and older euthyroid subjects.